THE URGENCY OF STRENGTHENING HALAL CERTIFICATION INSTITUTIONS AS A MEANS OF LEGAL PROTECTION FOR MUSLIM CONSUMERS IN SOUTHEAST ASIA - Trini Handayani,; Azzahra Salsabila Ramadani,; Nazwa St May,; Muhamad Fahri Mawardi, (Proceeding International Conference on Social Sciences, 2026)
Halal products are now a major necessity for the global community, both in Muslim and non-Muslim countries. However, the number of institutions authorised to issue halal certification at the global level is still very limited. This condition has resulted in suboptimal supervision of the halal supply chain. This study aims to analyse the concept of halal certification as an effort to provide protection and legal guarantees for Muslim consumers, while also examining the urgency of establishing and strengthening halal certification institutions in various countries. The method used is a descriptive narrative method with a qualitative approach. Meanwhile, the technique used to test the validity of the data is data triangulation. The results of the study show that the increasing demand for halal products in line with the growth of the global Muslim population requires an integrated halal supply chain system. Therefore, strengthening halal certification institutions in each country is important to ensure protection, legal certainty, and the trust of Muslim consumers in order to realise halal product guarantees with high quality standards.